Attitudes to English study among Japanese, Chinese and Korean women : motivations, expectations and identity - Kobayashi, Yoko, 1970- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This edited book comprises chapters integrated around a central theme on college-educated Japanese, Korean and Chinese women's orientation to English study. The collection is composed of two parts: the first part discusses the international migration facilitated by factors characteristic of East Asian nations. The second part sheds light on the dreams and realities of East Asian women who, having been avid English learners, aim for 'dream jobs' or have few other career choices but to be re-trained as English specialists or even as Japanese language teachers working abroad"--
Introduction / Yoko Kobayashi -- Study abroad, media and digital diaspora of Korean women / Youna Kim -- Japanese women's (re)negotiation of 'self/s' in Australian universities / Takae Ichimoto -- Going, returning or staying : Japanese women's motivations to study abroad / Eleni Oikonomidoy and Gwendolyn Williams -- Female language learners and workers : Japan versus its East Asian neighbors / Yoko Kobayashi -- Language as pure potential in Taiwan : case studies of six professional trajectories / Mark Seilhamer -- Dreams and realities : translating in South Korea / Jon H. Bahk-Halberg -- "How I wish English would actually save us women!" : anguish, ambivalence and agency among bilingual career women in Japan / Aya Kitamura -- Problems in the discourse of developing "Japanese who can play active roles around the world" : focusing on the life histories of English learners who turned into Japanese teachers / Nami Hirahata.
OCLC-licensed vendor bibliographic record.
Keywords: English language -- Study and teaching -- East Asia; English language -- Study and teaching -- Foreign speakers; English language -- Social aspects -- East Asia; Women -- East Asia -- Language; Women -- Education (Higher) -- English-speaking countries; East Asians -- Education (Higher) -- English-speaking countries; Bilingualism -- Social aspects -- East Asia; EDUCATION / Bilingual Education; EDUCATION / Adult & Continuing Education; EDUCATION / Language Experience Approach